Designed colostrum cake: Innovative process to prepare traditional indigenous milk product - Rahate, R S; Patil, Y N; Jagadale, SG; Kadav, VB; Dandekar, VS (Indian Journal of Dairy Science, 2022)
Colostrum is a traditional food having its health benefits to the human. The limited availability of natural colostrum, designed colostrum cake was prepared by blending egg-white, whey protein powder, Alphonso mango pulp, and other ingredients. In phase-I, six different mixes were prepared to optimize the level of egg-white and whey protein powder to be used for the preparation of the designed colostrum cake based on sensory evaluation. The treatment T3 having the combination of cow milk, egg-white, whey protein powder, and skim milk powder 50%, 15%, 10%, and 25% respectively were found to have the highest sensory score. In phase-II, Mango pulp was used @ 05, 10, 15, and 20 per cent of the colostral mix. It was found that among all the treatments addition of 15% alphonso mango pulp (T3) used with the most acceptable treatment T3 found in phase-I was recorded highest overall acceptability score of 8.07. This is followed by treatment T2 (7.84) while the lowest score was recorded of treatment T4 (7.50). The addition of Mango pulp in the designed colostrum cake improved sensory quality and overall acceptability. The most acceptable designed colostrum of 15% mango pulp recorded on an average total solid, fat, protein, ash, and acidity as 40.62, 2.55, 14.22, 2.31, and 0.38 per cent respectively. The cost of production of designed colostrum cake at T1, T2, T3, and T4 was  42.80,  43.10,  42.66, and  43.66 per 100 gm. The designed colostrum cake was successfully prepared with a high protein and low-fat content which further provides the scope to the food industries.